2017
DOI: 10.3847/1538-3881/aa7202
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Orbital Resonances on the Water Transport to Objects in the Circumprimary Habitable Zone of Binary Star Systems

Abstract: We investigate the role of secular and mean motion resonances on the water transport from a belt of icy asteroids onto planets or embryos orbiting inside the circumprimary habitable zone (HZ) of a binary star system. In addition, the host-star has an accompanying gas giant planet. For a comparison, we perform two case studies where a secular resonance (SR) is located either inside the HZ close to 1.0 au (causing eccentric motion of a planet or embryos therein) or in the asteroid belt, beyond the snow line. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…An important factor for the habitability of planets formed in the habitable zone is their water content which is strongly correlated to the gas giant and stellar companion's orbital and physical parameters (Haghighipour & Raymond 2007;Haghighipour et al 2010) leading to nearly dry planets in the HZ of the host star. However, a circumprimary icy asteroid belt can be the source of water for the entire habitable zone (Bancelin et al 2015(Bancelin et al , 2016 and for embryos or planets up to Earth distances (Bancelin et al 2017). In a future work, we aim to study how direct or indirect perturbation from passing stars can influence the water transport to a circumprimary habitable zone from circumstellar or circumbinary disks.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor for the habitability of planets formed in the habitable zone is their water content which is strongly correlated to the gas giant and stellar companion's orbital and physical parameters (Haghighipour & Raymond 2007;Haghighipour et al 2010) leading to nearly dry planets in the HZ of the host star. However, a circumprimary icy asteroid belt can be the source of water for the entire habitable zone (Bancelin et al 2015(Bancelin et al , 2016 and for embryos or planets up to Earth distances (Bancelin et al 2017). In a future work, we aim to study how direct or indirect perturbation from passing stars can influence the water transport to a circumprimary habitable zone from circumstellar or circumbinary disks.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can still provide an approximate estimate based on previous simulations involving small wet projectiles that impact planet-size targets. In Bancelin et al (2017) we studied the impact of rocky Ceres-size objects with a 15 wt-% water mass fraction on an Earth-sized planet at velocities ranging from 0.5 to 5 mutual escape velocities v esc . We find that at collision speeds of 0.5, 1, 3, and 5 v esc the water lost to space is 0, 11, 37, and 60 % of the initial water, respectively.…”
Section: Investigation Of One and Two Planetsmentioning
confidence: 99%
“…It is therefore appropriate to use the MOID for systems like Proxima Centauri where we don't know exactly the parameter space (planets and comets). For this purpose, we calculated the MOID after the numerical simulations as in Bancelin et al (2017) for each comet and estimated the impact probability: each close encounter between the comet and the planet was analyzed by sampling their true anomalies in order to derive impact distances. Trajectories with MOID < R Prox were classified as impacts, where R Prox corresponds to 1.08 Earth radii and is the estimated radius of PCb for an Earth-like composition (Brugger et al 2016).…”
Section: Water Transportmentioning
confidence: 99%
“…A weak point in all these numerical studies is certainly the treatment of collisions where usually the so-called perfect merging of two bodies is assumed without taking into account any fragmentation or mass-loss of the bodies due to the collision. However, Bancelin et al (2017) studied the collision parameters (impact angle and velocity) in tight binary stars and showed that the perfect merging approach can significantly overestimate the water content and mass of the formed planets. Thus, this simplified approach has to be replaced by a more realistic one that includes results of detailed collision simulations.…”
Section: Introductionmentioning
confidence: 99%